Analysis of Increased Induced Voltages on the Sheath of Double-Circuit Underground Transmission Lines Guaranteeing Ampacity - Asorza, Jesus Enrique Guevara; Leon Colqui, Jaimis Sajid; Kurokawa, Sérgio [UNESP]; Filho, José Pissolato (MDPI, 2024)
This paper quantifies and discusses the increase in induced voltage on a sheath due to changes in duct banks in terms of type and dimensions along an underground transmission line, guaranteeing the ampacity required for a project. The four most common duct banks in double-circuit underground transmission lines with phase transposition were considered in this study, along with two special cross-bonding techniques: continuous cross-bonding (CCB) and sectionalized cross-bonding (SCB). These techniques aim to reduce sheath currents and enhance the distribution of the induced voltage on the sheath. The analysis considers two distinct scenarios in which the profile of the induced voltage is calculated: the first one accounts for underground obstructions, intersections with important traffic avenues, and ground with high excavation costs that force changes in the duct bank dimensions and configuration, which is the most exact and realistic case. The second one solely considers one typical configuration of a duct bank along the route. This last scenario is normally applied to calculate the induced voltage when an underground transmission design is required. The results show that when installing cables at a greater depth, it is imperative to increase the distance between them to guarantee the ampacity. The induced voltage on the sheath will rise as the distance increases. Furthermore, the results reveal that instead of calculating the induced voltage by considering the scenario that is exact and most like a real case, it is enough to calculate following the second scenario and then add a scaling factor according to each duct bank configuration.
Keywords: ampacity; cross-bonding techniques; induced voltages; underground obstructions